2018
DOI: 10.2196/mhealth.8236
|View full text |Cite
|
Sign up to set email alerts
|

User Needs in the Development of a Health App Ecosystem for Self-Management of Cystic Fibrosis: User-Centered Development Approach

Abstract: BackgroundDigital self-management in cystic fibrosis (CF) is foreseen as a means toward better understanding of the disease and its treatment and better adherence to the treatment. Mobile apps hold the potential to provide access to information, motivate, and strengthen compliance. However, to deliver high-quality apps, the development should be based on thorough knowledge about user needs. Empirical research on the user-centered development of mobile apps for health care is, however, still limited.ObjectiveTh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…However, if well-managed people with CF are successfully able to live relatively independent lives, without constantly having to rely on interventions from health care professionals (HCPs). 21 The extent to which individuals with Cystic Fibrosis are able to manage their own care varies considerably over their life, depending on personal factors such as age, life-stage, emotional wellbeing and environmental factors such as where the individual lives and how much they earn (Floch et al 2018). This means that for the individuals over the course of their life, the amount and type of information that should be taken into account when making decisions about their care (and who is responsible for making these decisions) varies considerably.…”
Section: The Use Of Mhealth Tools By Those Living With Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, if well-managed people with CF are successfully able to live relatively independent lives, without constantly having to rely on interventions from health care professionals (HCPs). 21 The extent to which individuals with Cystic Fibrosis are able to manage their own care varies considerably over their life, depending on personal factors such as age, life-stage, emotional wellbeing and environmental factors such as where the individual lives and how much they earn (Floch et al 2018). This means that for the individuals over the course of their life, the amount and type of information that should be taken into account when making decisions about their care (and who is responsible for making these decisions) varies considerably.…”
Section: The Use Of Mhealth Tools By Those Living With Cystic Fibrosismentioning
confidence: 99%
“…age) and life changes (e.g. worsening of disease) and the associated adaptations in level of intervention (paternalism) required (Floch et al 2018).…”
Section: The Use Of Mhealth Tools By Those Living With Cystic Fibrosismentioning
confidence: 99%
“…Data 'co-interpretation' depends on aligning perspectives between patients, clinical staff, and other caregivers [44]. Information exchange can be compromised as patients and clinicians expect different forms of knowledge, and there is the need to bridge gaps in understanding rather than just share data [27]. These processes of information collection, synthesis and interpretation are particularly important in chronic conditions such as cystic fibrosis (CF), where clinical engagement is intermittent.…”
Section: Technology In Chronic Health Care Provisionmentioning
confidence: 99%
“…In addition to noting homogeneity in CF care structure across European countries, it found that existing apps for CF self-management only partially meet user needs [43]. A user-centered development approach identified a range of factors in a health app ecosystem for CF, including a readiness for selfmanagement, the diversity of user requirements (requiring personalization options), and the need for communication between patients and health care providers [27]. An investigation of gamification found that patients felt social interaction, empowerment, and progression through goals was important, alongside customization and adaptability to individual contexts [34].…”
Section: Cf Clinical Care Structure and Technologymentioning
confidence: 99%
“…The identification of user requirements as part of this process can lead to the development of HIT systems that are more successful in supporting patients with complex needs and symptoms. 26-28 Currently there is a lack of literature to guide method selection to support HIT systems for pain management in cancer care. 21 This report describes our experience of combining modern software development with health science research methods to create PainCheck, an HIT system designed to overcome known barriers to effective pain management for patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%